Malaysia : pembinaan negara dan bangsa - Zulhilmi Paidi; Rohani Ab Ghani; Mohamad Idris Saleh; Ismail Yusoff (Kuala Lumpur : Prentice Hall, 2011)
Politics and government of Malaysia.
Keywords: National characteristics, Malaysian; Civics, Malaysian; Malaysia -- Politics and government